Strategi Kepala Madrasah Dalam Motivasi Kerja Guru dan Iklim Organisasi Dalam Meningkatkan Mutu Madrasah - Agus Gunawan; Machdum Bachtiar; Anis Fauzi; Wahyudin Wahyudin (Peneliti.net, 2023)
Teachers must have good work motivation and organizational climate. However, the reality on the ground is still far from expectations. The results of observations of several educational institutions in Serang Regency, teachers lack a sense of togetherness between teachers, lack of cooperation between teachers, lack of motivation from the headmaster of the madrasa towards teachers and an uncomfortable school environment. The purpose of this study was to determine the strategy of the Madrasa Head in teacher work motivation and organizational climate to improve the quality of madrasas in MA Al-Muchlisin and MA Miftahul Ulum Kab. Attacks and constraints faced by Madrasah Heads in managing teacher work motivation and organizational climate to improve the quality of madrasas in MA Al-Muchlisin and MA Miftahul Ulum Kab. Attack. The benefits of this research Contributing and new knowledge to the world of education and enriching existing research and can provide an overview of the Madrasa Principal's Strategy in teacher work motivation and organizational climate to improve the quality of madrasas in MA Al-Muchlisin and MA Miftahul Ulum Kab. Attack. The conclusion of the research shows that the head of the madrasa has carried out several strategies of the head of the madrasa in terms of teacher work motivation and organizational climate to improve the quality of education including improving the quality of teacher and student education, both academic and non-academic education, improving the quality and professionalism of teachers and other school staff, as well as improvement and infrastructure of school infrastructure in the form of education in accordance with their interests. And there are several obstacles faced by madrasa heads in terms of teacher work motivation and organizational climate to improve the quality of education in MA Al-Muchlisin and MA Miftahul Ulum Kab. Serang, in essence, there is a lack of welfare provided so that the teacher is not comfortable and the facilities and infrastructure are inadequate, the teacher feels dissatisfied with the provision of a salary that has not been able to meet the needs of daily life.